Analisis Variasi Penangguhan Penanganan Sampel Darah Edta Terhadap Hasil Pemeriksaan Hitung Jumlah Trombosit dengan Metode Brecher Chonkrite Pada Mahasiswa Diii Analis Kesehatan Universitas Indonesia Timur - Nurul Utami Halimsyah (Jurnal Media Laboran, 2017)
This research is motivated by checking the number of platelets that must be done as soon as possible and not more than 2 hours. The purpose of this study is to see whether there is a significant difference to the Counting of Platelet Count by Using Brecher Chonkrite Method with EDTA Blood Sampling for 1, 2 and 3 Hours at Diploma Three of Health Analyst University of Eastern Indonesia. This research is a quasi experiment with sampling technique by accidental sampling. From the research done on 20 samples, we get the data of platelet count before and after 2 hours that Fcount (-37,22) <Ftabel (8,57) meaning there is no significant difference to the result of the count count of the platelet count of brecher chonkrite method with variation Suspension time of 1 hour, 2 hours and 3 hours. It is suggested that on hematology examination specially on counting blood platelet counts using EDTA samples can be suspended with a delay of 1, 2 and 3 hours. But it would be nice that the sample to be examined is not suspended, because it can cause a decrease in platelet count even though the decrease did not experience a significant difference.